(untitled) (PerCursos, 2024)
This article aims to reflect on repressive education as the foundation of capitalist society that, in a latent or real way, is permeated in its social and political structure by violence. The theoretical contribution is the historical materialism of Antonio Gramsci’ writings, for which the way of life and the forms of collective organization live a permanent formative process. We begin with the political writings from 1916 to 1920, in which the reflection on the censorship exercised by the Italian State in the period of the First World War, the resurgence of reaction and violence when the order of capital loses control of the productive forces, to the pressure permanent political struggle and subsequent ostensive repression of the fascist movement. Next, we recover in notes the author’s reflections on repressive education in Prison Letters.